2019
DOI: 10.1055/a-0961-2371
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine und Z-Substanzen – Analyse der kassenärztlichen Verschreibungen von 2006 bis 2015

Abstract: ZusammenfassungEs wird untersucht, wie sich die kassenärztlichen Verschreibungen von Benzodiazepinen (BZD) und Z-Substanzen (ZS) über einen 10-Jahres-Zeitraum entwickelt haben. GKV-Rezepte des Norddeutschen Apotheken-Rechenzentrums (NARZ) wurden für Schleswig-Holstein, Hamburg, Niedersachsen und Bremen von 2006 – 2015 ausgewertet. 1,64 Mio. Patienten erhielten Verschreibungen von BZD und/oder ZS im 10-Jahres-Zeitraum. 65,3 % sind Frauen, über die Hälfte sind 60 Jahre oder älter. Der Anteil an Patienten mit lei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The decreasing trend in the intake of hypnotics/ sedative and the small amount of fluctuation in the numbers of associated dependence disorders point to a possible delayed positive effect. This development is confirmed by a recent study based on an evaluation of prescriptions supplied to statutorily insured patients (40). According to the authors, the numbers of persons receiving prescriptions for benzodiazepines and z-drugs and the numbers of prescriptions that deviate from guidelines are decreasing in the statutorily insured population.…”
Section: Medicationsmentioning
confidence: 74%
“…The decreasing trend in the intake of hypnotics/ sedative and the small amount of fluctuation in the numbers of associated dependence disorders point to a possible delayed positive effect. This development is confirmed by a recent study based on an evaluation of prescriptions supplied to statutorily insured patients (40). According to the authors, the numbers of persons receiving prescriptions for benzodiazepines and z-drugs and the numbers of prescriptions that deviate from guidelines are decreasing in the statutorily insured population.…”
Section: Medicationsmentioning
confidence: 74%
“…In most countries use of benzodiazepines increases with age and is more common among women 20–24 . A systematic review by Votaw et al found conflicting reports on whether benzodiazepine misuse was associated with age or gender 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the likelihood of multiple types of physicians being involved – especially anaesthesiologists who are the specialists in pain management – increases with the number of prescriptions. Indeed, receiving OA prescriptions from several doctors (for non-medical use) appears to play a less important role compared with benzodiazepines (BZD) or Z-drug prescriptions ( Verthein et al, 2019 ). Also, Hulme et al (2018) found in their meta-analysis that the main source of pharmaceutical opioids for non-medical use are friends and family and that illegitimate practices such as ‘doctor shopping’ are mainly uncommon.…”
Section: Discussionmentioning
confidence: 99%